2016
DOI: 10.2967/jnumed.115.167858
|View full text |Cite
|
Sign up to set email alerts
|

Glial Activation and Glucose Metabolism in a Transgenic Amyloid Mouse Model: A Triple-Tracer PET Study

Abstract: Amyloid imaging by small-animal PET in models of Alzheimer disease (AD) offers the possibility to track amyloidogenesis and brain energy metabolism. Because microglial activation is thought to contribute to AD pathology, we undertook a triple-tracer smallanimal PET study to assess microglial activation and glucose metabolism in association with amyloid plaque load in a transgenic AD mouse model. Methods: Groups of PS2APP and C57BL/6 wildtype mice of various ages were examined by small-animal PET. We acquired 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
173
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(196 citation statements)
references
References 31 publications
22
173
1
Order By: Relevance
“…In line with previous results Brendel et al, 2016), we found an agedependent increase in TSPO lPET signal in wild-type mice (Fig 5A and B). To do so, we conducted a longitudinal study (3, 5, 8, and 12 months) using the PET tracer [ 18 ]F-GE180 (18-kD translocator protein ligand [TSPO]) for imaging activated microglia in vivo by lPET.…”
Section: Exaggerated Immune Response To In Vivo Lipopolysaccharide Stsupporting
confidence: 93%
“…In line with previous results Brendel et al, 2016), we found an agedependent increase in TSPO lPET signal in wild-type mice (Fig 5A and B). To do so, we conducted a longitudinal study (3, 5, 8, and 12 months) using the PET tracer [ 18 ]F-GE180 (18-kD translocator protein ligand [TSPO]) for imaging activated microglia in vivo by lPET.…”
Section: Exaggerated Immune Response To In Vivo Lipopolysaccharide Stsupporting
confidence: 93%
“…28-31 These studies observed increases in 18 F-FDG at younger ages, while in older mice either there were no changes compared to WT or there were increases. The 5-time familial AD (5×FAD) mouse model exhibit increases at younger ages, but there were decreases of 18 F-FDG uptake at ages older than 13 months.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, 18 F-FDG imaging detected age-dependent decreases in the tauopathy mouse model tauVLW (37) and thus may be more applicable in models with tau pathology. Because activated glial cells also take up 18 have demonstrated age-related increases in PS2APP, APPPS1-d9, 5xFAD, and TG mouse models (33,39). Additionally, chronic BACE inhibitor treatment (NB-360) has previously been shown to reduce glial cells in APP51/16 mice (12), and thus we herein evaluated the ability of 18 F-PBR111 to detect changes in neuroinflammation in response to disease and treatment.…”
Section: Discussionmentioning
confidence: 99%